Bűn és büntetés a középkori egyházban - Balogh, Elemér (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2024)
The medieval Latin Church had a very clear and elaborate theory of human sin and the punishment that was necessarily associated with it. This complex thought can be summarised in two main theories: theological theory and canon law, which can be particularly well illustrated by means of case law, i.e. the activity of the ecclesiastical courts. In the following overview, I will present the legal basis and purpose of punishment, as well as the types of punishment, based on the theological views of Thomas Aquinas on the one hand, and on the sources of medieval canon law on the other, illustrated with examples from canonical jurisdiction.